2006
DOI: 10.1016/j.euje.2006.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Contrast-enhanced tissue Doppler imaging of the left atrial appendage is a new quantitative measure of spontaneous echocardiographic contrast in atrial fibrillation

Abstract: Contrast-enhanced TDI is an original new tool that provides a quantification of the mean velocity of LAA-SEC that might improve our decision making in patients with atrial fibrillation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 33 publications
0
13
1
Order By: Relevance
“…58 In cases where spontaneous echo contrast may render the identification of thrombi difficult, tissue Doppler imaging with or without echocardiographic contrast injection may improve thrombus detection. 59 Beyond detection of thrombus, TEE provides assessment of LAA structure. 3D TEE has been shown to be superior to 2D TEE for delineation of LAA geometry, which has obvious implications for LAA closure device implantation.…”
Section: La Appendagementioning
confidence: 99%
“…58 In cases where spontaneous echo contrast may render the identification of thrombi difficult, tissue Doppler imaging with or without echocardiographic contrast injection may improve thrombus detection. 59 Beyond detection of thrombus, TEE provides assessment of LAA structure. 3D TEE has been shown to be superior to 2D TEE for delineation of LAA geometry, which has obvious implications for LAA closure device implantation.…”
Section: La Appendagementioning
confidence: 99%
“…It has been deemed to be "our most lethal attachment" taking into account the morbidity and mortality of cardiogenic embolism [49]. Low blood flow velocities within the LAA [57] are associated with the occurence of spontaneous echo contrast (SEC) [22,78,96] and a procoagulatory milieu [7] which is strongly associated with LAA thrombus formation and systemical embolism [51,108]. Therefore, LAA flow velocities and SEC density have been considered as surrogate parameters for stroke risk stratification and may help in case of doubt to decide in favor or against warfarin [37].…”
Section: The Concept Of Laa Closure For Prophylaxis Of Thromboembolismentioning
confidence: 99%
“…Further improvement of B-mode image quality of 3D-TOE will be available in the near future. The combination of tissue doppler imaging and use of contrast agents may help to better characterize thrombogenic structures within the LAA 58). Also, with respect to LAA imaging, few studies using MRI and spiral CT scan have been reported on detection of thrombus and SEC 38)39)143-146).…”
Section: Cardiac Imaging For Thrombus Detectionmentioning
confidence: 99%